Fragile states and insecure people? violence, security, and statehood in the twenty-first century - Andersen, Louise; Moller, Bjorn; Stepputat, Finn (Palgrave studies in governance, security, and development, 2007)
This book provides a unique account of the pursuit of security at the edge of global order. It sheds light on reform of state police and armed forces, and analyzes the alternative security structures that emerge in the absence of the state.